2016
DOI: 10.3171/2015.12.peds15388
|View full text |Cite
|
Sign up to set email alerts
|

The Preventable Shunt Revision Rate: a potential quality metric for pediatric shunt surgery

Abstract: OBJECTIVE Shunt surgery consumes a large amount of pediatric neurosurgical health care resources. Although many studies have sought to identify risk factors for shunt failure, there is no consensus within the literature on variables that are predictive or protective. In this era of “quality outcome measures,” some authors have proposed various metrics to assess quality outcomes for shunt surgery. In this paper, the Preventable Shunt Revision Rate (PSRR) is proposed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Within the subset of our unplanned reoperations, the majority (73.5%) were shunt related. Recently, Venable et al 13 attempted to refine the analysis of shunt-related reoperations by focusing on the "Preventable Shunt Revision Rate." Preventable failure included infection, a malpositioned proximal or distal catheter, or an inadequately secured valve.…”
Section: Areas For Improvementmentioning
confidence: 99%
“…Within the subset of our unplanned reoperations, the majority (73.5%) were shunt related. Recently, Venable et al 13 attempted to refine the analysis of shunt-related reoperations by focusing on the "Preventable Shunt Revision Rate." Preventable failure included infection, a malpositioned proximal or distal catheter, or an inadequately secured valve.…”
Section: Areas For Improvementmentioning
confidence: 99%
“…It has been proposed that the preventable shunt revision rate could be a quality metric used for external comparison in the pediatric population. [ 23 24 25 ] In the adult population, the preventable unplanned shunt implantation return rate has also been proposed as a possible external comparison quality metric. [26] Reviewing the literature on UROR related to CSF diversion, Mukerji et al [13] and Roy et al [12] previously reported that shunt-related procedures accounted for 44% and 40.8% of all pediatric procedures at their study institutions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Venable GT et al 15 reviewed 525 patients with 927 shunt insertion or revision surgeries. They studied risk factors comparing preventable and non-preventable causes.…”
Section: All the Included Patients Required One Or More Shuntmentioning
confidence: 99%